2020
DOI: 10.2967/jnumed.120.245605
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA PET/CT for Primary Lymph Node and Distant Metastasis NM Staging of High-Risk Prostate Cancer

Abstract: With the largest high-risk prostate cancer (PCa) cohort to date undergoing 68 Ga-prostate-specific membrane antigen (PSMA) PET/CT primary staging, we aimed to 1) characterize the metastatic spread of PCa in relation to tumor 68 Ga-PSMA-uptake and the D'Amico classification, and 2) compare 68 Ga-PSMA PET/CT findings with radical prostatectomy (RP) with pelvic lymph node dissection (PLND) histopathology. Methods A total of 691 consecutive newly diagnosed, biopsy-proven, treatment-naïve, D'Amico high-risk PCa pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 29 publications
6
41
0
Order By: Relevance
“…The primary tumour prostate-specific membrane antigen (PSMA) expression was also reported to correlate with the dominant intraprostatic lesion ISUP GG in a number of studies, however with substantial overlap between groups [45][46][47][48][49]. A direct comparison between 82 Rb and PSMA PET is needed to determine which physiologic parameter is closest related to the tumour aggressiveness and how they relate to each other.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The primary tumour prostate-specific membrane antigen (PSMA) expression was also reported to correlate with the dominant intraprostatic lesion ISUP GG in a number of studies, however with substantial overlap between groups [45][46][47][48][49]. A direct comparison between 82 Rb and PSMA PET is needed to determine which physiologic parameter is closest related to the tumour aggressiveness and how they relate to each other.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Following the removal of duplicates, 307 records were screened by titles and abstracts, and 40 studies were deemed relevant for full-text assessment. Ultimately, 11 studies ( 21 31 ) fulfilled the inclusion criteria and were included in the meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 11 studies comprising 904 patients who underwent 68 Ga-PSMA PET/CT before RP with PLND were included. All studies recruited patients with confirmed PCa of intermediate/high risk, and three studies ( 25 , 26 , 31 ) additionally applied nomogram tools ( 9 , 32 ) to identify patients of high risk of lymph node metastases. All studies set 68 Ga-PSMA PET/CT imaging as an index test and defined a positive test with increased 68 Ga-PSMA uptake above background.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations